Suppose f : R → R is a function given by
f ( x ) = ⎩ ⎨ ⎧ 1 e ( x 1 0 − 1 ) + ( x − 1 ) 2 sin x − 1 1 if x = 1 if x = 1
Evaluate u → ∞ lim [ 1 0 0 u − u k = 1 ∑ 1 0 0 f ( 1 + u k ) ]
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Fisrt assume that f is differentiable at x = 1 and that f ′ ( 1 ) = 1 0
Then, ∀ k ∈ N , f ( 1 + x k ) x → + ∞ = 1 + 1 0 x k + o ( x 1 )
So, because the sum is finite,
x k = 1 ∑ 1 0 0 f ( 1 + x k ) x → + ∞ = x k = 1 ∑ 1 0 0 [ 1 + 1 0 x k + o ( x 1 ) ] x → + ∞ = 1 0 0 x + k = 1 ∑ 1 0 0 1 0 k + o ( 1 ) x → + ∞ = 1 0 0 x + 5 0 5 0 0 + o ( 1 )
Thus the answer is − 5 0 5 0 0
Proof that f is differentiable at x = 1 and that f ′ ( 1 ) = 1 0
Let g : R → R defined by g ( x ) = x 2 sin ( x 1 ) if x = 0 and g ( 0 ) = 0 .
g is continuous and differentiable at x = 1 because:
∣ g ( x ) ∣ ≤ x 2 x → 0 ⟶ 0 = g ( 0 )
And ∣ x − 0 g ( x ) − g ( 0 ) ∣ = ∣ x sin ( x 1 ) ∣ ≤ ∣ x ∣ x → 0 ⟶ 0
Therefore g is differentiable at x = 1 and g ′ ( 0 ) = 0 . So obviously, h = g ∘ ( i d − 1 ) is differentiable at x = 1 and h ′ ( 1 ) = 0 .
This proves that f is differentiable at x = 1 and f ′ ( 1 ) = d x d e x 1 0 − 1 ∣ x = 1 = 1 0 x 9 e x 1 0 − 1 ∣ x = 1 = 1 0 □